Depth of relationship counseling review counselor version - Sisca Folastri; M. Ramli (Konselor, 2022)
The depth of the relationship in counseling is key in determining the success of counseling.  The method used in this study is the  survey  method.  The sample in the study involved as many as 36 counselors.  The instrument used is the  Rational Depth Frequency Scale (RDFS). The  data analysis technique uses Rasch  modeling with the winstep program  version 4.45.  Researchhas  revealed that in general counselors have a depth of relationship in the counseling process. Where the counselor in the moment of depth of the relationship feels intense security, genuineness, empathy, and positive acceptance in the counseling process. The counselor feels what the counselor is going through, the counselor openly conveys his problems because of the counselor's warm and pleasant acceptance attitude. The depth of the counselor relationship  in the counseling process  as one of  the  factors  of success and effectiveness of counseling. The results of  this study can be used as preliminary data  to examine more deeply the  depth of the relationship in the counseling  process  in terms of  counseling